Engineering cartilage or endochondral bone: A comparison of different naturally derived hydrogels. - VINARDELL, TATIANA; KELLY, DANIEL (My University, 2015)
Cartilaginous tissues engineered using mesenchymal stem cells (MSCs) have been shown to generate bone in vivo by executing an endochondral programme. This may hinder the use of MSCs for articular cartilage regeneration, but opens the possibility of using engineered cartilaginous tissues for large bone defect repair. Hydrogels may be an attractive tool in the scaling-up of such tissue engineered grafts for endochondral bone regeneration. In this study, we compared the capacity of different naturally derived hydrogels (alginate, chitosan and fibrin) to support chondrogenesis and hypertrophy of MSCs in vitro and endochondral ossification in vivo. In vitro, alginate and chitosan constructs accumulated the highest levels of sulfated glycosaminoglycan (sGAG), with chitosan constructs synthesizing the highest levels of collagen. Alginate and fibrin constructs supported the greatest degree of calcium accumulation, though only fibrin constructs calcified homogeneously. In vivo, chitosan constructs facilitated neither vascularization nor endochondral ossification, and also retained the greatest amount of sGAG, suggesting it to be a more suitable material for the engineering of articular cartilage. Both alginate and fibrin constructs facilitated vascularization and endochondral bone formation as well as the development of a bone marrow environment. Alginate constructs accumulated significantly more mineral and supported greater bone formation in central regions of the engineered tissue. In conclusion, this study demonstrates the capacity of chitosan hydrogels to promote and better maintain a chondrogenic phenotype in MSCs and highlights the potential of utilizing alginate hydrogels for MSC-based endochondral bone tissue engineering applications.
PUBLISHED
Keywords: Mesenchymal stem cell; Hydrogel; Fibrin; Endochondral ossification; Chitosan; Alginate; Next Generation Medical Devices; Mechanical Engineering